ACCOUNTING STUDENTS' PERCEPTIONS OF TAX EVASION: RELIGIOSITY AS A POTENTIAL FACTOR - Erawati, Teguh; Harun, Silvana (Jurnal Aplikasi Akuntansi, 2026)
This investigation examines the influence of religiosity, tax knowledge, and tax fairness on accounting students' perceptions of tax evasion. Grounded in the Theory of Planned Behavior (TPB), this research addresses the critical role of future accountants as ethical gatekeepers. A quantitative explanatory design was employed, involving 90 accounting students from Universitas Sarjanawiyata Tamansiswa (2019–2022 cohorts) selected via purposive sampling. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The findings demonstrate that religiosity and tax knowledge significantly and negatively influence perceptions of tax evasion, indicating that strong spiritual anchors and cognitive proficiency enhance ethical rejection of fraudulent practices. Conversely, tax fairness was found to have a significant positive effect on perceptions of tax evasion. This "fairness paradox" suggests that while procedural justice is acknowledged, a perceived lack of distributive justice may lead students to rationalize evasion as a response to systemic mismanagement. These outcomes highlight the necessity for tax authorities to demonstrate outcome-based accountability and for educational institutions to integrate character-building frameworks, particularly Tamansiswa values, to fortify professional integrity.